Effect of the Use of Graphic Media on the Learning Outcomes of Indonesian Language Subjects Instructional Text Material of Class IV Students MI Almunazomah Caringin District, Bogor Regency - Nur Hurriyatul Kamila; Nuryansyah Adijaya (Mitra Palupi, 2022)
Background: The use of media in the learning process can facilitate the process of communication or delivery of messages from teachers to students. Students can clearly understand the instruction meaning or message that the teacher conveys. Purpose: This study aims to determine the learning outcomes of students using graphic media and the effect of using graphic media on student learning outcomes in Indonesian subjects for class IV instructional texts at MI Almunazomah, Caringin District, Bogor Regency. Design and methods: This research is an experimental research. The subjects of this study were all fourth-grade students, totalling 20 people. The test instrument used to determine student learning outcomes is a multiple choice test in the form of pre-test and post-test. Results: The results of this study indicate that the experimental group taught using graphic media obtained an average pre-test average value post-test of 77 with a standard deviation of 16.36. Changes in learning outcomes are 42 by using graphic media. While the mean value of the pre-test in the control group was 37 with a standard deviation of 13.37 and the average value of the post-test was 52 with a standard deviation of 14.76. Changes in learning outcomes are 15 without using graphic media. Based on the hypothesis testing criteria at = 0.05, t observe = 3.59 and t table = 2.10 so that t observe > t table or 3.59 > 2.19 then Ha is accepted and Ho is rejected. It can be concluded that there is a significant effect of the use of graphic media on the learning outcomes of fourth grade students in the Indonesian subject of instructional text material at MI Almunazomah, Caringin District, Bogor Regency.